A City Full of Life or a City Buried Alive? Vittorio Alfieri’s Venice and Venice in the Travel Journals by Polish Artists at the Turn of the 19th Century - Szadkowska-Mańkowska, Olga (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2020)
The article raises the topic of the evolving image of Venice from the perspectives of three travel accounts: by Vittorio Alfieri, Fryderyk August Moszyński, and Stanisław Dunin-Borkowski. They were all bound by the figure of the Italian playwright Alfieri. In the article, I propose a new look into the accounts from the travels of Polish intellectual elite: an enlightened journey described in the recollections by Moszyński, and a 19th-century journey depicted in the journals by Borkowski, following Alfieri as the guide. Considering his tragedies in support of national liberation, he perfectly matched the ideas in the minds of Polish artists at the turn of the 19th century. Even though the author may be forgotten today, the reception of his works, depending on the historical period, political situation, and literary streams, evolved interchangeably placing him in the spotlight and ignoring him. In the first half of the 19th century, he was a significant figure, a fact which triggers interesting observations, particularly in the context of the journeys of artists to Venice.